1998
DOI: 10.1055/s-0037-1615395
|View full text |Cite
|
Sign up to set email alerts
|

4G/5G Polymorphism of PAI-1 Gene Promoter and Fibrinolytic Capacity in Patients with Deep Vein Thrombosis

Abstract: SummaryA deletion/insertion polymorphism (4G or 5G) in the promoter of the plasminogen activator inhibitor type 1 gene has been suggested to be involved in regulation of the synthesis of the inhibitor, the 4G allele being associated with enhanced gene expression. A relationship between 4G/5G polymorphism and PAI-1 levels was found in patients with cardiovascular and metabolic diseases, but not in healthy subjects. In the present work we studied the distribution of PAI-1 4G/5G geno-type and its relation to fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
3
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 40 publications
2
61
3
4
Order By: Relevance
“…The 4G allele frequency (0´48) and the distribution of PAI-1 4G/ 5G genotypes in control subjects were not significantly different from those reported previously (Ridker et al, 1997;Sartori et al, 1998;Stegnar et al, 1998). The prevalence of the 4G allele was higher in the case group than among control subjects (x 2 8´00, P 0´005).…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…The 4G allele frequency (0´48) and the distribution of PAI-1 4G/ 5G genotypes in control subjects were not significantly different from those reported previously (Ridker et al, 1997;Sartori et al, 1998;Stegnar et al, 1998). The prevalence of the 4G allele was higher in the case group than among control subjects (x 2 8´00, P 0´005).…”
Section: Resultscontrasting
confidence: 52%
“…However, patients possessing the 4G allele were shown to have significantly increased levels of PAI-1 activity and antigen when compared with healthy controls with the same genotype (Stegnar et al, 1998). Similarly, Sartori et al (1998) demonstrated a PAI-1-induced hypofibrinolysis among deep vein thrombosis patients that was strongly related to the presence of the 4G allele. These last studies suggest that possession of the 4G allele is associated with a reduced fibrinolytic potential that may be pathological in patients with deep vein thrombosis.…”
Section: Discussionmentioning
confidence: 89%
“…In unselected patients with DVT, no association between the 4G/5G polymorphism and the development of VTE was observed in several different studies, 7,13,14 in contrast to the findings of Sartori et al, 12 who reported a significantly lower 5G/5G prevalence in DVT patients compared with healthy individuals, without, however, any statistically significant difference in allele frequencies between the 2 groups. On the other hand, in selected populations with an established genetic risk factor for VT, such as protein S deficiency or FV Leiden, concurrence of homozygosity for the 4G allele led to an increased risk for VT.…”
Section: Morange Et Al Pai-1 Gene Polymorphisms and Fv Leidenmentioning
confidence: 71%
“…7,8,10 Although several studies have suggested a contribution from the Ϫ675 4G/5G variant in myocardial infarction development, 6,9,11 very few data are available on the relations between PAI-1 polymorphisms and the occurrence of VT. Except for 1 study, 12 most have not found any relationship between the Ϫ675 4G/5G polymorphism and the development of VT in unselected patients. 7,13,14 However, the Ϫ675 4G/4G genotype has been shown to be linked to an increased risk for VT in patients with protein S deficiency 15 or in small series of FV Leiden carriers.…”
mentioning
confidence: 83%
“…[14][15][16] Studies on PAI-1 levels have yielded conflicting results. 17,18 In the 1980s various epidemiological studies were undertaken using assays to determine overall fibrinolytic potential, such as the euglobulin clot lysis time (ECLT) and dilute whole blood clot lysis time (DWBCLT). As the CLT measured by these assays did not seem to be related to the risk of venous thrombosis, 19 the interest in fibrinolysis decreased and the dissolution of the blood clot was put to one side as a phenomenon secondary to coagulation.…”
Section: Hypofibrinolysis As a Risk Factor For Venous Thrombosismentioning
confidence: 99%